2002
DOI: 10.1001/jama.287.4.487
|View full text |Cite
|
Sign up to set email alerts
|

The Hospitalist Movement 5 Years Later

Abstract: Empirical research supports the premise that hospitalists improve inpatient efficiency without harmful effects on quality or patient satisfaction. Education may be improved. In part catalyzed by these data, the clinical use of hospitalists is growing rapidly, and hospitalists are also assuming prominent roles as teachers, researchers, and quality leaders. The hospitalist field has now achieved many of the attributes of traditional medical specialties and seems destined to continue to grow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
294
1
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(303 citation statements)
references
References 46 publications
1
294
1
7
Order By: Relevance
“…Although teaching team assignment appears random, because allocation is not concealed, we considered this a quasi-experimental design. 13,14 Eighteen hospitalist and 61 non-hospitalist faculty serve as ward teaching attending physicians, and are assigned to teaching teams in one-month blocks. Because we hypothesized that premature discharge might cause harm among patients under the care of short LOS physicians, we attributed each admission to the discharging attending physician, whom we assumed was the final arbiter of the decision to discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Although teaching team assignment appears random, because allocation is not concealed, we considered this a quasi-experimental design. 13,14 Eighteen hospitalist and 61 non-hospitalist faculty serve as ward teaching attending physicians, and are assigned to teaching teams in one-month blocks. Because we hypothesized that premature discharge might cause harm among patients under the care of short LOS physicians, we attributed each admission to the discharging attending physician, whom we assumed was the final arbiter of the decision to discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Commonly, hospital-based physicians, including hospitalists, and medical and surgical residents in academic institutions, work exclusively in the hospital and care for the majority of hospitalized patients. [20][21][22][23][24][25][26] Oftentimes, the hospital physician is first introduced to their patient at hospital admission and must rely on the history, physical exam and medical record when making medical decisions. [27][28][29][30][31] For this reason, the hospital physician may be unaware of a patient's drug or alcohol use or mental illness, all risk factors for opioid misuse.…”
Section: Introductionmentioning
confidence: 99%
“…The number of years in practice (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and 21+ years) was included instead of age, as those two variables were highly correlated. Time spent in email or phone conversation with other physicians was included to measure each physician's level of communication.…”
Section: Methodsmentioning
confidence: 99%
“…One widely discussed advantage is that hospitalists can contain hospital costs and improve inpatient efficiency. 3 Several studies have shown that successful hospitalist programs improved inpatient efficiency without harmful effects on quality. [4][5][6][7] Proponents contend that successful hospitalist programs have the potential to improve outpatient primary care physicians' (PCPs' ) productivity because hospitalists can reduce the need for PCPs to go to the hospital, allowing them to see more patients in the office than was previously possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation